SEA TOLL AS A MEANS TO INCREASE THE EFFECTIVENESS OF GOODS AND SERVICES TO THE EASTERN OF INDONESIA - RATNAWATI, ELFRIDA (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
The large price difference between the western, central and eastern regions of Indonesia is a problem that must be solved is the ineffective and inefficient distribution of the goods and services resulting contribution in high transportation costs and the impact on the price of goods. Sea Toll is a concept of sea transportation about the marine logistics system that aims to connect one large port to other major ports in Indonesia, supported by sea transportation to operate non-stop from Sabang to Merauke so that the economy move efficiently and evenly, the sea toll has great benefits to support Indonesia's economy as a maritime nation. What is the role of the sea toll as an alternative to support the smooth transportation of goods and services to eastern Indonesia? And what are the benefits obtained after the implementation of the sea toll in Indonesia for eastern Indonesia? Those are the main problems in this research. The purpose of this study is to describe the role of the sea toll as an alternative to support the smooth transport of goods and services in Indonesia and the benefits of the sea toll as a driver of the Indonesian economy and the results of sea toll activities in the Eastern Indonesia region in particular. Normative research, supported by primary and secondary data and then analyzed descriptively through a qualitative approach is an understanding of an issue using questionnaires and respondents. The role of the sea toll as an alternative to support the smooth transportation of goods and services to drive the Indonesian economy so that it is evenly distributed throughout Indonesia, especially in the eastern region, therefore needs to be supported by good regulations and the impact of the implementation of sea toll for eastern Indonesia, although the results have not been too maximal, but the regional community eastern Indonesia has felt a rapid decline in prices even nearly equaling market prices in other regions of Indonesia, thus the Government's goal of prospering its people is achieved.